2001
DOI: 10.1081/erc-100107179
|View full text |Cite
|
Sign up to set email alerts
|

PREVALENCE AND COMPARISONS OF FIVE DIFFERENT DIAGNOSTIC METHODS FORHELICOBACTER PYLORIIN DIABETIC PATIENTS

Abstract: Helicobacter pylori is now regarded as a major gastroduodenal pathogen that is etiologically linked with duodenal and gastric disease. It has been suggested recently as an important factor for nongastroenterologic conditions such as coronary heart disease and diabetes mellitus. In this study, we planned to investigate the prevalence of H. pylori in diabetic patients and to evaluate five different diagnostic tests. Group I consisted of 67 patients with type II diabetes mellitus and seventy-three aged-matched he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 16 publications
1
21
0
2
Order By: Relevance
“…The high prevalence of H. pylori infection in patients with diabetes is generally explained by reduced gastric motility and peristaltic activity which may promote H. pylori colonization [22], various chemical changes in gastric mucosa following non-enzymatic glycosylation of mucins or increased sialic acid [23] which may be involved as a receptor for H. pylori on the cell surface by promoting adhesion of H. pylori to gastric mucosa cells [24] and an impaired non-specific immunity observed in patients with diabetes [25]. …”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of H. pylori infection in patients with diabetes is generally explained by reduced gastric motility and peristaltic activity which may promote H. pylori colonization [22], various chemical changes in gastric mucosa following non-enzymatic glycosylation of mucins or increased sialic acid [23] which may be involved as a receptor for H. pylori on the cell surface by promoting adhesion of H. pylori to gastric mucosa cells [24] and an impaired non-specific immunity observed in patients with diabetes [25]. …”
Section: Discussionmentioning
confidence: 99%
“…Although culture of the organism and histological examination have been used as gold standards, 24,25 long‐term growth of the organism in culture, human errors in interpretation of the biopsy results and cost‐effectiveness issues restricted wide use of these tests as reference examinations 25,26 . No single test, therefore, was used as the gold standard, the same approach as that used previously 10,18,19,27 . Thus, Hp status was defined as the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies [22,23] have demonstrated the reliability of H. pylori tests used before treatment, while post-treatment testing is not yet adequately studied. However, in the case of long-lasting recurrent dyspepsia after H. pylori eradication therapy, endoscopy has been strongly recommended [4].…”
Section: Discussionmentioning
confidence: 99%